2020
DOI: 10.4012/dmj.2019-053
|View full text |Cite
|
Sign up to set email alerts
|

Enamel preservation during composite removal after orthodontic debonding comparing hydroabrasion with rotary instruments

Abstract: The aim of the present study was to evaluate how hydroabrasion performs during composite removal. A standardized amount of composite was bonded to 40 enamel surfaces of extracted third molars, then removed with either a tungsten carbide bur mounted on a micro-motor handpiece without irrigation, a tungsten carbide bur mounted on a micro-motor handpiece with irrigation, a tungsten carbide bur mounted on an air-rotor handpiece, or hydroabrasion. The four treatment methods were compared using the enamelsurface-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
(23 reference statements)
5
15
0
Order By: Relevance
“…No significantly different results between the adhesive removal protocols tested in the current study were obtained for the time spent to remove resin remnants from enamel surfaces. Less time might be spent for TCB group, if a high-speed rotary system was selected, but more damage to the enamel surface should be expected, similar to previous studies [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 74%
“…No significantly different results between the adhesive removal protocols tested in the current study were obtained for the time spent to remove resin remnants from enamel surfaces. Less time might be spent for TCB group, if a high-speed rotary system was selected, but more damage to the enamel surface should be expected, similar to previous studies [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 74%
“…The advantage of this feature is that minimum amounts of resin are adhered to the enamel after debonding, reducing the required time to remove the residual adhesive. In the contrary, some reports suggested a potential enamel damage during debonding (Bosco et al, 2020), because its composition may promote more enamel damage when SBS values are higher (Cruz-González & Delgado-Mejía, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Some authors reported that etching with phosphoric acid removes only the inorganic part of the enamel, while the organic matrix is left intact—and this is a difference compared to air abrasion or hydroabrasion—and can be remineralized, thus resulting in a minimal net loss of enamel [ 22 ]. However, this is true only if the etched enamel receives no further treatment: indeed, if a layer of resin adhesive is applied to it, then the choice is between accepting leaving adhesive remnants on the tooth surface or removing that amount of enamel together with the adhesive, as demonstrated by different studies [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Air-abrasion has some drawbacks, mostly due to the dispersion of aluminum oxide particles in the patient's mouth and around the operative field, which requires the use of protective eyewear for both the operator and the patient: such limits have been overcome by hydroabrasion, a technique where the powder is propelled by an air and water spray, which helps control the dissemination of the aluminum particles [17]. Hydroabrasion has already been described as a viable method for composite removal after orthodontic debonding [18], but to the knowledge of the authors of the present work, no data are available regarding its use as a method for enamel conditioning before orthodontic bonding of metal brackets. Therefore, the aim of the present study was to evaluate in vitro the shear bond strength and the adhesive remnant index on extracted teeth after three methods of enamel conditioning: acid etching; hydroabrasion; and a combination of hydroabrasion and acid etching.…”
Section: Introductionmentioning
confidence: 99%